-4u(u-5)(u-4)=0

Simple and best practice solution for -4u(u-5)(u-4)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4u(u-5)(u-4)=0 equation:


Simplifying
-4u(u + -5)(u + -4) = 0

Reorder the terms:
-4u(-5 + u)(u + -4) = 0

Reorder the terms:
-4u(-5 + u)(-4 + u) = 0

Multiply (-5 + u) * (-4 + u)
-4u(-5(-4 + u) + u(-4 + u)) = 0
-4u((-4 * -5 + u * -5) + u(-4 + u)) = 0
-4u((20 + -5u) + u(-4 + u)) = 0
-4u(20 + -5u + (-4 * u + u * u)) = 0
-4u(20 + -5u + (-4u + u2)) = 0

Combine like terms: -5u + -4u = -9u
-4u(20 + -9u + u2) = 0
(20 * -4u + -9u * -4u + u2 * -4u) = 0
(-80u + 36u2 + -4u3) = 0

Solving
-80u + 36u2 + -4u3 = 0

Solving for variable 'u'.

Factor out the Greatest Common Factor (GCF), '4u'.
4u(-20 + 9u + -1u2) = 0

Factor a trinomial.
4u((-5 + u)(4 + -1u)) = 0

Ignore the factor 4.

Subproblem 1

Set the factor 'u' equal to zero and attempt to solve: Simplifying u = 0 Solving u = 0 Move all terms containing u to the left, all other terms to the right. Simplifying u = 0

Subproblem 2

Set the factor '(-5 + u)' equal to zero and attempt to solve: Simplifying -5 + u = 0 Solving -5 + u = 0 Move all terms containing u to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + u = 0 + 5 Combine like terms: -5 + 5 = 0 0 + u = 0 + 5 u = 0 + 5 Combine like terms: 0 + 5 = 5 u = 5 Simplifying u = 5

Subproblem 3

Set the factor '(4 + -1u)' equal to zero and attempt to solve: Simplifying 4 + -1u = 0 Solving 4 + -1u = 0 Move all terms containing u to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1u = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1u = 0 + -4 -1u = 0 + -4 Combine like terms: 0 + -4 = -4 -1u = -4 Divide each side by '-1'. u = 4 Simplifying u = 4

Solution

u = {0, 5, 4}

See similar equations:

| x(x+6)(x+-4)=24x | | -68-9x=127+6x | | A=1020(1-0.0195)15 | | X+(x+12)=5x | | 12m+5=6+1m | | 13y+15=39 | | 3.2+0.3(18)=0.2(18)+1.4 | | 7(6-4P)+2P= | | -(n-3)+7(3+n)-2n+7n= | | 3(7q+6)=3q | | 3-4k=11 | | -8(1m-6)=88 | | -13m=-3777 | | 2.4(m-3)+8=-8.2 | | 58=2thirdw | | -4(-5n-4)=-144 | | 7(4+3x)=196+3x | | -x+3=40 | | (2x+1)+(3x-3)+(9x)=180 | | 5x-2d+1=15 | | 2=-11k | | A=1020(1-0.195)15 | | -x-3=16 | | 29x+160=73 | | y=0.23x+27 | | 10x+260-5x=450 | | A=1020(1-0.0195)20 | | 16x+14=39 | | x^2-6+34=0 | | 4p+7=3+4+4p | | -6x^2+5x-(6x^2-5x+6)= | | 13-16=3y+6-2y |

Equations solver categories